The effect of copper casting on the optical properties of the ZNFE2O4 zinc membranes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this research ,the effect of the copper doping on Optical properties of zinc Firrete precipitated on the glass Substrate of quartz have been studied,with  ratios of Cu (0,1,3,5,7and9%) using the method of chemical spray Payrolysis of thickness(300 ± 15nm) at a temperature (400 ± 10 oC) and annealing (520 oC) for range of (4h) the Optical properties have been identified of films wavelengths of (300-900) nm , it has been found that the energy gap before doping(2.86 eV) the energy gap increased to increase the proportion of doping the ratios (1,3and 5%) the energy gap at ratios (7 and9%) also found that the highest value of the refractive index at doping ratios (0,09) and value (2.65) and the coefficient of absorption at the ratio (0.09) and the value of(3x104), Extinction at a Ratio (0.09) and the value of (0.125).